Trichoderma Technology and Uses - Cezar Juliatti, Fernando (IntechOpen, 2022)
This book discusses Trichoderma spp. and its molecular aspects and mode of action on important plant pathogens. In Brazil, there are already more than thirty-four species of this fungus registered in commercial products to control soil-borne pathogens. The book also discusses industrial use of Trichoderma. Chapters examine the application of the fungus in the integrated management of plant diseases as well as its general use in bioprocesses and even in the alcohol production industry for biofuels.